Overcoming a Communication Barrier on the Way Towards a Global Sensor Network - Furthmüller, Jochen; Pink, Mario; Hartenstein, Hannes; Waldhorst, Oliver (Electronic Communications of the EASST, 2009)
In a global sensor network different sensor platforms will be deployed. A grave obstacle on the way of building sensor networks out of different sensor nodes are incompatible implementations of network protocol stacks used with different sensor node platforms. We describe our efforts to overcome this obstacle in a heterogeneous sensor network consisting out of MICAz Motes and Sun SPOTs, both using an IEEE 802.15.4 radio chip. We explain the major differences in the respective network stacks and our approach to bridge them. A network stack that bridges the gap between different platforms allows for more flexible and robust networks.